Synthesis of Biodiesel from Avocado Seed Oil Transesterification Method Using Beef Bone Catalyst - Fajar, Dimas Rizqi; Baihaqi, Muhammad Yusril; Maharani, Natalia Nada; Salim, Soma (Department of Chemistry Faculty of Science and Technology Walisongo, 2023)
Avocado seeds have a relatively high content of Fatty Acid Methyl Ester, so they have the potential to be used as raw material for biodiesel. The process of processing biodiesel from avocado seeds is through a transesterification reaction, using a heterogeneous catalyst in the form of a stable bovine bone and green technology. This study uses a cow bone catalyst to produce biodiesel from avocado seed oil through a transesterification process. Biodiesel has characteristics; density of 0.75 g/cm3, FFA 0.468%, and acid number 0.732 mg-KOH/g. The transesterification process at 60° for 1 hour obtained an FFA of 1.50% to 0.468% and yield biodiesel 28.8%. The research showed that all biodiesel quality tests at SNI 04-7182-2015 except for the quality density test. The FTIR results of biodiesel are: wave number 2585-2956 cm-1 C-C (alkane) asymmetrical stretching shows free fatty acid chain bonds, 1749.88 cm-1 Carbonyl ester group C=O, peak-C-H group wavelength at 1459 cm-1, The position of the carbonyl ester is strengthened by the presence of the C-O ester position at a wavelength at 1378 cm-1, the C-H group (alkane) with a length at 1060 cm-1.